A Gain Enhanced Metasurface based Monopole Antenna for WLAN Application - Samantaray D.; Bhattacharyya S. (My University, 2025)
The design and performance of a highly directive gain enhanced metasurface antenna (MSA) has been reported in this paper. The MSA is formed by incorporating the T-shaped patch with 3times 5 order metasurface (MS) in which the MS is associated with annular hexagonal shaped patches arranging in periodic manner. This antenna operates at 4.99 GHz and the-10 dB impedance bandwidth has been achieved in the range 4.79 GHz-5.09 GHz. The antenna provides the maximum realized gain of 11.2 dBi at 4.99 GHz. The endfire radiation pattern has been observed along E-plane while nearly omnidirectional pattern has been realized along H-plane. The designed structure can be promoted for WLAN applications. © 2021 URSI.